Pluriactivity, entrepreneurship and socio-economic success of rural households - Ranmuthumalie De Silva; Sarath S. Kodithuwakku (The University of Manchester, Manchester Business School, 2010)
Pluriactivity has been identified in literature as a capital accumulation strategy. However, it has also been recognized as a survival strategy particularly in a resource constrained environment. Accordingly, it is questionable as to what extent pluriactivitity leads households to be socio-economically better off. This leads to the question 'in a given context, whether certain other factors such as motive and entrepreneurial qualities also play a role in determining the success besides being pluriactive?'. This debate has a greater significance particularly in rural contexts of developing countries since a transformation from a traditional agricultural based rural economy to a more diversified economy has been observed in the past few decades. Accordingly, it is intended to address this issue through research carried out to compare and contrast better-off and worse-off pluriactive households in a given locality in Sri Lanka based on their motive to become pluriactive (pull and/or push), the portfolio of income generation activities carried out and their entrepreneurial qualities. Multiple data collection methods were used and the data were analyzed qualitatively. The findings were supplemented with quantifiable evidence when necessary in order to increase the validity of the conclusions.The study site was a typical example of a resource constrained environment and pluriactivity has been identified as a strategy implemented by both income groups in order to increase their household resources. For better-off households, being pluriactive was initially due to push motives which have later been transformed into pull motives. In contrast, for worse-off households being pluriactive has always been a push motive. The better-off households have diversified into more off-farm income generation activities and hence their dependency on agriculture was lower than that of worse-off households who were mainly dependant on agricultural related diversification. In addition, the better-off households exhibited more entrepreneurial qualities as they extract values from the environment without regard to the resources owned by them. Based on these patterns, it could be concluded that being motivated by pull factors (at least after some years of initiation), diversifying into off-farm income generation activities and being entrepreneurial have paved the way for pluriactive rural households to be socio-economically better-off.
Keywords: 330